Odpowiedzi

2010-04-11T17:15:11+02:00
9y-11=6y+7
9y-6y=7+11
3y=18
y=18:3
y=6

18-8y=5y-y
-8y-5y+y=-18
-12y=-18
y=-18: (-12)
y=1,5

-21-3s=-17-12s
-3s+12s=-17+21
9s=4
s=4:9
s= 0, (4)
1 1 1
Najlepsza Odpowiedź!
2010-04-11T17:18:03+02:00
9y-11=6y+7
3y=18
y=6
L=9*(6)-11=43
P=6*(6)+7=43
L=P

18-8y=5y-y
18-8y=4y
-4y=-18
y=4,5
L= 18 - 8*(4.5) =18
P= 5*(4,5) - 4,5=18
L=P


-21-3s=-17-12s
-3s+12s=-17+21
9s=4
s=4/9
L=-21 - 3*(4/9)= -21 - 1 1/3 = -22 1/3
P= -17 - 12 * (4/9) = -17 - 5 1/3 = -22 1/3
L=P
1 2 1